2019
DOI: 10.1039/c8cc10306b
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Rh(ii) and Yb(iii) catalyzed synthesis of substituted naphthofurans via transannulation of N-sulfonyl-1,2,3-triazoles with β-naphthols

Abstract: Synthesis of substituted naphthofurans has been achieved via an efficient cascade Rh(ii)/Yb(iii) catalyzed transannulation of N-sulfonyl-1,2,3-triazoles with β-naphthols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…A similar but step-economic approach to access benzofurans was reported by Kang and co-workers through Rh­(II)- and Cu­(I)-catalyzed sequential sp 3 C–H insertion and aerobic oxidation (path C) . A Rh­(II)-catalyzed O–H insertion followed by Yb­(III)-catalyzed cyclization and oxidation sequence of triazoles and phenols was reported by Anbarasan and co-workers for the synthesis of benzo/naphthofurans (path D) . Despite these efficient methods, the development of novel synthetic methods for the construction of benzofurans is still desirable, and herein, we report a new protocol to prepare benzofurans via a Rh­(II)-catalyzed denitrogenative cascade process.…”
mentioning
confidence: 84%
“…A similar but step-economic approach to access benzofurans was reported by Kang and co-workers through Rh­(II)- and Cu­(I)-catalyzed sequential sp 3 C–H insertion and aerobic oxidation (path C) . A Rh­(II)-catalyzed O–H insertion followed by Yb­(III)-catalyzed cyclization and oxidation sequence of triazoles and phenols was reported by Anbarasan and co-workers for the synthesis of benzo/naphthofurans (path D) . Despite these efficient methods, the development of novel synthetic methods for the construction of benzofurans is still desirable, and herein, we report a new protocol to prepare benzofurans via a Rh­(II)-catalyzed denitrogenative cascade process.…”
mentioning
confidence: 84%
“…Subsequently, in 2019, we reported the cascade Rh(II) and Yb(III)-catalyzed synthesis of naphthofurans 62 from ßnaphthol 61 and triazoles 45 in the presence of oxygen atmosphere (Scheme 12). [24] The reaction goes through initial OÀ H insertion to generate 63 in the presence of rhodium catalyst followed by enamide and imine tautomerization delivers the imine 64. Formation of product 62 was rationalized through ytterbium-catalyzed cyclization of imine to give 64 followed by aromatization-cum-oxidation in the presence of molecular oxygen.…”
Section: Reaction With Oxygen Nucleophilesmentioning
confidence: 99%
“…In 2019, Anbarasan group demonstrated that azavinyl carbene could also be inserted into the OÀ H bond of βnaphthols 124 for the construction of substituted naphthofurans 127 (Scheme 28). [47] The one-pot dual catalytic cascade process involved Rh(II) catalyzed 1,3-insertion of carbene into the OÀ H bond followed by Yb(III) catalyzed intramolecular annulation and subsequent aerial oxidation to access an array of 1-aminonaphthofurans in moderate to good yields. The reaction scope was broad as various triazoles and β-naphthols/ phenols could be used in this reaction.…”
Section: Oà H Nà H Insertionmentioning
confidence: 99%